2022
DOI: 10.3390/metabo12040295
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging (MRI) and MR Spectroscopic Methods in Understanding Breast Cancer Biology and Metabolism

Abstract: A common malignancy that affects women is breast cancer. It is the second leading cause of cancer-related death among women. Metabolic reprogramming occurs during cancer growth, invasion, and metastases. Functional magnetic resonance (MR) methods comprising an array of techniques have shown potential for illustrating physiological and molecular processes changes before anatomical manifestations on conventional MR imaging. Among these, in vivo proton (1H) MR spectroscopy (MRS) is widely used for differentiating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 166 publications
0
19
0
Order By: Relevance
“…Nevertheless, such applications are still in the technical development phase and are far from being incorporated into clinical practice [22-24, and 38 ].Third, MRI technology has evolved and proton MR spectroscopy and diffusion weighting can also affect false-positive results. However, these techniques require a longer acquisition time and have a substantial number of technical aws, such as voxel shift, incomplete acquisition, or incorrect shimming, and therefore, their performance was not evaluated in our study [39,40]. Last but not least, false positives may be affected depending on the indication of the MRI study, and therefore, our study focused primarily on high-risk patients may not be transferable to other settings.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, such applications are still in the technical development phase and are far from being incorporated into clinical practice [22-24, and 38 ].Third, MRI technology has evolved and proton MR spectroscopy and diffusion weighting can also affect false-positive results. However, these techniques require a longer acquisition time and have a substantial number of technical aws, such as voxel shift, incomplete acquisition, or incorrect shimming, and therefore, their performance was not evaluated in our study [39,40]. Last but not least, false positives may be affected depending on the indication of the MRI study, and therefore, our study focused primarily on high-risk patients may not be transferable to other settings.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, sensitivity and specificity of MRS for distinguishing benign and malignant lesions was found to be 89.6% and 91.2% respectively (Thakur and Bitencourt, 2022). A study investigated use of MRS along with MRI for diagnosis of breast lesions (Sharma and Jagannathan, 2022). In this study, women with suspicious breast mass of 1 cm diameter were examined.…”
Section: Discussionmentioning
confidence: 96%
“…Although mammography is cost effective, it has some limitations such as discomfort breast compression and radiation exposure. On the other hand, a study by Sharma et al [25] showed that MRI achieves 96.2% sensitivity and 83.3% for clinical response and pathological respectively. However, MRI is not effective for breast cancer detection as specificity to lesion characteristics remains low, rendering distinction between cancer and benign pathology a challenge [26] .…”
Section: Conventional Breast Cancer Diagnosis Techniquesmentioning
confidence: 96%